1993
DOI: 10.1159/000163780
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Tissue Kallikrein in Normal and SV40-Transfected Human Endometrial Stromal Cells

Abstract: The polymerase chain reaction with specific tissue kallikrein primers was utilized to demonstrate the presence of tissue kallikrein mRNA in human endometrial stromal cells. Enzymatic analysis measured with a specific tripeptide nitroanilide substrate demonstrated the presence of tissue kallikrein in the conditioned medium obtained from both normal stromal cells and stromal cells transfected with an origin-defective temperature-sensitive SV40 large T antigen. The transfected stromal cell supernatant exhibited a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Elevated levels of tissue kallikrein, however, are correlated with the pathogenesis of asthma, arthritis, and inflammatory articular diseases (9 -11). Tissue kallikrein is also identified in colon and breast cancer cells and may be involved in malignant transformation by stimulating proliferation of tumor cells and increasing vascular permeability (12)(13)(14)(15). Development of a specific and selective inhibitor to tissue kallikrein would be critical for studies of various biological functions of tissue kallikrein and potential therapies for certain inflammatory disorders and carcinomas.…”
mentioning
confidence: 99%
“…Elevated levels of tissue kallikrein, however, are correlated with the pathogenesis of asthma, arthritis, and inflammatory articular diseases (9 -11). Tissue kallikrein is also identified in colon and breast cancer cells and may be involved in malignant transformation by stimulating proliferation of tumor cells and increasing vascular permeability (12)(13)(14)(15). Development of a specific and selective inhibitor to tissue kallikrein would be critical for studies of various biological functions of tissue kallikrein and potential therapies for certain inflammatory disorders and carcinomas.…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that the human tissue kallikrein gene (or KLK1) is expressed in the endometrial tissue of the human uterus (Wu et al, 1993;Clements et al, 1997;Valdès et al, 2001). Interestingly, the levels of Klk1 expression in the human endometrium are elevated midcycle, at a time when the estrogen levels are elevated and extensive endometrial proliferation occurs in preparation for implantation, and then fall in the latter part of the secretory phase of the menstrual cycle, at a time of rising progesterone levels .…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of these factors in synovial fluid of arthritic joints, bronchial lavage fluid of asthmatics, and nasal secretions of patients with allergic rhinitis have implicated tissue kallikrein in the pathogenesis of asthma, arthritis, and inflammatory articular diseases (Worthy et al, 1990;Forteza et al, 1996;Volpe-Junior et al, 1996). Tissue kallikrein has also been identified in human colon and breast cancer cells and may be involved in malignant transformation of certain cells (Wu et al, 1993;Chen et al, 1995;Hermann et al, 1995;Rehbock et al, 1995;Koshikawa et al, 1996). Thus, tissue kallikrein is an attractive target toward which to develop inhibitors for potential therapies for some inflammatory disorders or for some cancers.…”
mentioning
confidence: 99%